Modification of the prediction model of the tensile strength of short fiber reinforced polymer composites. Issue 1 (February 2020) - Zhu, Z H; Zhang, N; Zhang, Y; Hao, M Y; Wu, H W
Abstract: Based on the defect of COX model, the parameters related to the interface properties were introduced, and the fitting results were modified to be closer to the measured values.